Improved Anti-Oxidant and Anti-Bacterial Capacities of Skim Milk Fermented by Lactobacillus plantarum - Wang, Ying; Zhao, Bingtian; Ding, Yun; Liu, Nan; Yang, Cheng; Sun, Yajuan (Molecules (Basel, Switzerland), 2024)
Milk, on account of its abundant protein content, is recognized as a vital source of bioactive substances. In this study, the bioactive ingredients in milk were obtained by a combination of protease hydrolysis and fermentation with Lactobacillus plantarum. The compositions of protease hydrolysate (PM) and fermentation supernatant (FM) were determined, and their anti-oxidant and anti-bacterial activities were evaluated. Using LC-MS/MS, the molecular weights and sequences of the peptides were characterized, among which a total of 25 bioactive peptides were identified. The DPPH radical scavenging results demonstrated that FM exhibited an enhanced anti-oxidant capacity compared to PM. The bacterial survival rate results revealed that FM had a remarkable anti-bacterial ability compared to PM. Additionally, the anti-bacterial component and potential anti-bacterial mechanisms were determined. The results of cytoplasmic membrane depolarization, cell membrane permeability, and morphological observation indicated that FM could interact with bacterial membranes to achieve its anti-bacterial effect. These findings suggested that FM, as a bioactive substance of natural origin, holds potential applications in the functional food, pharmaceutical, and cosmetic industries.